From bats to bees: changes in flower anthesis and nectar traits drive a pollination ecotype in dwarf Caryocar brasiliense (Caryocaraceae) - Ballarin, Caio Simões [UNESP]; Lacerda-Barbosa, Pedro Augusto [UNESP]; Moraes, Ana Paula [UNESP]; Campos, Felipe Girotto [UNESP]; Amorim, Felipe Wanderley [UNESP] (Oxford University Press, 2025)
Background and Aims Widespread plants often display different phenotypes that influence pollination. In the Brazilian Cerrado, Caryocar brasiliense typically grows as a bat-pollinated tree, but a hemicryptophyte dwarf form occurs in a population near the southern limit of the Cerrado distribution in Brazil, where large-bodied bees are the main visitors. We investigated whether these forms represent distinct pollination ecotypes and assessed the ecological drivers and the potential role of polyploidy underlying their divergence. Methods We compared floral traits associated with pollinator attraction and reward (flower size, anthesis timing, nectar dynamics and chemical composition) between forms. Pollinator exclusion experiments evaluated the effectiveness of diurnal and nocturnal visitors. Genome size and chromosome number were assessed to explore the role of polyploidy in trait divergence. Key Results The dwarf form had smaller flowers, later anthesis and nectar secretion peaking in the early morning, with sucrose-enriched, hexose-dominant nectar. Bee visitation rates were over 50 times higher than bat visits and positively associated with nectar sugar content. Diurnal visitors, especially large bees, significantly increased fruit and seed set. Genome size and chromosome number were consistent across ecotypes, suggesting no polyploidy. Conclusions A shift from bat to bee pollination in the dwarf form of C. brasiliense appears to be driven by changes in floral traits, rather than by polyploidy or absence of bat pollinators. This highlights the importance of anthesis timing and nectar chemical composition in shaping pollinator-mediated divergence across heterogeneous landscapes.
De morcegos a abelhas: mudanças na antese floral e nos atributos do néctar direcionam um ecótipo de polinização em Caryocar brasiliense anão (Caryocaraceae)
Keywords: Bee pollination; Cerrado; Chiropterophilous; Nectar dynamics; Neotropical savanna; Pollinator shift; Polinização por abelhas; Ecologia do cerrado; Polinizadores